Z dziejów polskich przymiotników znaczących ‘chytry’ - Krótki, Zuzanna (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2016)
In the article there were analyzed etymologically and semantically 37 names of adjectives ‘crafty’ in the Old Polish lexicology. The material was gathered from all available lexicographical sources registering the vocabulary to the end of 19th century. It was evidenced that the formal structures investigated adjectives implied pictures such as: the picture of grasping at something, a picture of efficiency and excellence in particular field, the image of vector of change movement, the picture of phatamorgana, deception of something duplicitous, the figure of something hidden. Moreover the gross of analyzed units found its place in noun-derivation group of actions manifesting – cunningness or created in the ‘noun place’ with figurative sense. The implemented analysis depicted the differences between old Polish and the contemporary Polish language demonstrating itself on the par with lexicology and semantics.